TATHBIQ AL-ISITIRATIJIYAH AL-ISTIQSHAIYAH FI TARQIYAH NATAIJ TADRIS AL-MUFRADAT - Fajar Pinastiya Arrahman; Syamsul Arifin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
The success of students in the class depended on the expertise of teachers in teaching and learning strategies which were influential in boosting students’ learning interest and motivation. This research aimed to understand the weakness of the application of their strategy and analyze any constraints at the time of the application as well as the values the students suggested after the application of the strategy. The research was a classroom action research which covered planning, implementing, observing, and reflecting. After implementing the strategy, the researchers gained the values of students rose in every cycle.